Ovarian transcriptomic analysis reveals differential expression genes associated with cell death process after selection for ovulation rate in rabbits - Serna‐garcía, Marta [UNESP]; Peiró, Rosa; Serna, Eva; Santacreu, María Antonia (MDPI, 2020)
Litter size is an essential trait in rabbit meat production but with low heritability. A selection experiment for ovulation rate has been performed for 10 generations to improve litter size in rabbits. The selected line increased two ova more than the control line but nevertheless a negative correlation was observed with prenatal survival. A transcriptomic study was performed, using microarrays, in ovarian tissue from females belonging to the selected line and the control line. Our results showed 1357 differential expressed genes and nineteen potential biomarkers associated with prenatal mortality, which could explain differences between litter size in rabbits. Cell death was the most relevant process.
Keywords: Litter size; Ovarian tissue; Ovulation rate; Rabbit; Transcriptomic analysis